2020
DOI: 10.1111/php.13297
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flow Reactor for the Controlled Synthesis and Inline Photocatalysis of Antibacterial Ag2S Nanoparticles

Abstract: The present study is focused on the integration of microreactors to synthesize visible light active nanophotocatalysts for inline photocatalytic degradation of organic dye and antibacterial activity. A wire‐assisted and a rapid laser micromachining technique has been employed for the fabrication of polydimethylsiloxane (PDMS) and poly(methyl methacrylate) (PMMA)‐based microreactors, respectively. By varying the design and chemical reagents involved, different sizes of visible light active Ag2S nanoparticles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The stability of the SnO 2 –AgBr (1 : 1) composite is related to its practicability and is also an important factor to measure its photocatalytic performance. 71,72 After four cycles of experiment, the degradation rates of MO and MG decreased to 66.42% and 70.86%, respectively (Fig. 11a and b).…”
Section: Resultsmentioning
confidence: 94%
“…The stability of the SnO 2 –AgBr (1 : 1) composite is related to its practicability and is also an important factor to measure its photocatalytic performance. 71,72 After four cycles of experiment, the degradation rates of MO and MG decreased to 66.42% and 70.86%, respectively (Fig. 11a and b).…”
Section: Resultsmentioning
confidence: 94%
“…Some attempts also have been made to utilize microreactor in the synthesis of Ag 2 S QDs [14] . Bhanu Prakash et al synthesized QDs in milliliter-scale microchannels [15] . Whereas, the slower mass transfer in the laminar-flow dominated microchannel resulted in less new nucleation of crystals, and larger the average size of QDs (about 15 nm) which severely exceeded the natural filtration threshold in living organisms (5 nm) [16] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, microfluidic technology has attracted increasing attention across various fields due to its precise control and high operational efficiency. Enhanced mass transfer within the microchannel enables the continuous execution of certain synthetic processes, thus ameliorating the productivity of products traditionally inefficient in complex batch operations. Segmented flow, one of the most studied flow patterns in microfluidics, features a vortex in each segment, facilitating robust internal recirculation and superior mass and heat transfer. Owing to this attribute, segmented flow has been utilized not only in chemical reactions but also in extraction and crystallization procedures. In our previous study, we effectively regulated the length of the gas–liquid segment in a 1.59 mm perfluoroalkoxy (PFA) tube without varying the fluid flow rates . We further demonstrated that mass transfer at the segment interface is significantly enhanced relative to that at the bubble surface, and the rate of mass transfer can be modulated by altering the segment length, a topic to be elaborated upon in our upcoming publication.…”
Section: Introductionmentioning
confidence: 99%